On approximating fixed points of a new class of generalized nonexpansive mappings in uniformly convex hyperbolic space - Nazlı Kadıoğlu Karaca (MANAS: Journal of Engineering)
In this paper, we introduce the definition of a new class of generalized nonexpansivemappings in hyperbolic space. Additionally, we construct the rewritten version ofthe Mann iteration process in hyperbolic space. Then, using the iterative procedurewe established, we prove convergence theorems for 𝑎−𝑏−generalized nonexpansivemappings in a uniformly convex hyperbolic space. Lastly, we offer a numericalexample to illustrate our findings.